Perceived Social Support and Cardiovascular Risk Among Nonelderly Adults in the United States - Datta, Biplab Kumar; Coughlin, Steven S.; Gummadi, Aneesha; Mehrabian, Daniel; Ansa, Benjamin E. (The American journal of cardiology, 2023)
Hypertension, diabetes mellitus, dyslipidemia, and obesity are major risk factors of cardiovascular diseases. A recent study projected a marked surge in these cardiometabolic conditions in the United States by the year 2060, posing a challenge for cardiovascular disease management in the coming years. This study aimed to explore and quantify the relation of a key psychosocial factor, social support, with the cardiovascular risk factors among nonelderly US adults (aged 18 to 64 years). Using data on 19,827 adults from the 2021 National Health Interview Survey, we assessed whether lower level of social support was associated with higher likelihood of having cardiovascular risks. We found that for subjects who “rarely/never” received social support, the adjusted odds of having hypertension, high cholesterol, and diabetes were 1.42 (95% confidence interval [CI] 1.20 to 1.67), 1.39 (95% CI 1.18 to 1.65), and 1.53 (95% CI 1.22 to 1.91) times those of subjects “always” receiving support, respectively. Further, compared with the base outcome of no CV risk, the adjusted relative risks of having 3+ cardiovascular risks for subjects “rarely/never” receiving support were 1.91 (95% CI 1.49 to 2.46) times that of those “always” receiving support. These results were robust across socioeconomic status condition sub-groups manifested by educational attainment and income. In conclusion, our findings suggest that social support may be considered as a critical part of the comprehensive efforts to mitigate the future burden of cardiovascular diseases in the United States.